In Vitro Modulation of Glibenclamide Transport by P-glycoprotein Inhibitory Antidiabetic African Plant Extracts - Ezuruike, Udoamaka F.; Chieli, Elisabetta; Prieto, Jose M. (Planta Medica, 2019)
The rise of diabetes incidence in Nigeria enhances the use of popular remedies that may interact with conventional therapies. The aqueous extracts of 27 popular Nigerian “antidiabetic” plants were tested for their in vitro effects on glutathione levels within HepG2 cells, P-glycoprotein (P-gp)-mediated Rh-123 efflux activity in Caco-2 vincristine-resistant cells, and modulation of glibenclamide transport in Caco-2 monolayers. The extract from Ximenia americana significantly depleted intracellular glutathione at 100 µg/mL similarly to the reference buthionine sulphoximine (p < 0.05). Other 10 extracts raised glutathione levels. Eight extracts inhibiting P-gp efflux in a concentration-dependent manner (p < 0.01) were selected for further evaluation in a bi-directional transport model across Caco-2 monolayers: Annona senegalensis, Bridellia ferruginea, Cassytha filiformis, Daniellia ogea, Khaya ivorensis, Syzygium guineense, Terminalia avicennioides, and X. americana. When interferences in paracellular transport were discarded, only 3 of them may be modulating the efflux ratio of glibenclamide (efflux ratio: 2.65 ± 0.13) in the same manner the reference drug verapamil (efflux ratio: 1.14 ± 0.25, p < 0.01) does: Syzygium guineense (efflux ratio: 1.70 ± 0.23, p < 0.01), Terminalia avicennioides (efflux ratio: 1.80 ± 0.25, p < 0.05), and X. americana (efflux ratio: 1.66 ± 0.10, p < 0.01). HPLC-UV analyses for P-gp inhibitors in these extracts revealed several phenolic compounds such as rutin, gallic acid, and ellagic acid reported to decrease P-gp expression and/or directly modify its function. In conclusion, some popular herbal medicines used by Nigerian diabetic patients are here shown to potentially affect glibenclamide absorption at concentrations that could be reached in the intestinal tract.
Keywords: diabetes; drug interactions; P-glycoprotein; glyburide; glutathione; Syzygium guineense; Terminalia avicennioides; Ximenia Americana